The Potential of Floating Markets for Creative Tourism: A Study in Nakhon Pathom Province, Thailand - Walanchalee Wattanacharoensil (2018)
© 2015 Asia Pacific Tourism Association. This article examines the potential of floating markets in the Nakhon Pathom province as a creative tourism destination by performing a two-stage qualitative study. It explores in particular the perceptions of community leaders toward the possibility for established floating markets to become creative tourism destinations and the current and future constraints in such development. In the first stage, an environmental scanning is performed using readiness indices for tourism destination, which are adopted from two sources. In the second stage, the perceptions of community leaders toward floating markets are examined through in-depth, semi-structured interviews. These investigations reveal the significant role of community leaders and their perspectives toward the direction and development of their communities. The investigations also identify the factors that promote and obstruct creative tourism in a particular floating market destination.